Development of the Multi-Level Approval Feature in the SIMASTER Leave Application Module for Bungo Regency - Ahadi, Ahmad Husna; Aminuddin, Fattachul Huda; Gustina; Anzari, Yandi (Jurnal Teknologi Informatika dan Komputer, 2025)
Effective and efficient personnel administration services are an urgent need for government agencies to improve the quality of governance of the State Civil Apparatus. The Bungo Regency Government has developed an integrated system for all Regional Apparatus Organizations (OPD) called the Integrated ASN Management Information System (SIMASTER). One of the important services in SIMASTER is leave applications, which currently rely on a single level of approval, namely by the OPD admin. This mechanism is deemed not to fully reflect the government bureaucratic structure and has the potential to reduce accountability in the leave application process. Therefore, development is needed to implement a tiered approval feature in accordance with the flow of leave applications based on established rules. This study aims to design and implement a tiered approval feature in the leave application module in the Bungo Regency Integrated ASN Management Information System (SIMASTER). This development is expected to make the leave application process more transparent, structured, and accountable. The system development method used in this study was a prototype method. Testing was conducted using black box testing with the equivalence partitioning technique. The results showed that the developed system performed well, as measured by the trial phase using the black box testing method. A recommendation is to add a notification feature so that all processes can be immediately communicated to relevant parties.